A Multilevel SPH Solver with Unified Solid Boundary Handling. (27th October 2016) - Takahashi, Tetsuya; Lin, Ming C.
Abstract: We propose a geometric multilevel solver for efficiently solving linear systems arising from particle‐based methods. To apply this method to particle systems, we construct the hierarchy, establish the correspondence between solutions at the particle and grid levels, and coarsen simulation elements taking boundary conditions into account. In addition, we propose a new solid boundary handling method to solve a pressure Poisson equation in a unified manner. We demonstrate that our method can handle general fluid simulation scenarios including two‐way fluid‐solid coupling, and the computational cost of this new solver scales nearly linearly with respect to the number of unknowns, unlike previous solvers for particle‐based methods.